(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The rule of Andalusia during the period(138-172 AH/756-788 AD), the Umayyad prince Abdul Rahman bin Muawiya bin Hisham bin Abdul Malik, nicknamed Al- dakhl, who survived the oppression of the Abbasids and managed to establish an Umayyad Emirates in Andalusia separate from the Abbasid Caliphate in Baghdad, but not soon That Andalusia faced during the reign of Prince Abdul Rahman, a number of internal risks and challenges aimed at its security and civilization and therefore the Islamic presence in it represents the most serious revolutions against him, which supported by the Abbasid caliphate in Baghdad, which led to negative results for the Muslim Arabs in Andalusia. حكم الأندلس خلال الفترة (138-172هـ / 756-788م)، الأمير الأموي عبد الرحمن بن معاوية بن هشام بن عبد الملك الملقب بالداخل ، الذي نجا من بطش العباسيين وتمكن من تأسيس إمارة أموية في الأندلس منفصلة عن الخلافة العباسية في بغداد، ولكن لم تلبث أن واجهت الأندلس خلال عهد الأمير عبد الرحمن، جملة من المخاطر والتحديات الداخلية التي استهدفت أمنها وحضارتها وبالتالي الوجود الإسلامي فيها تمثل أخطرها بالثورات التي قامت ضده والتي دُعمت من قبل الخلافة العباسية ببغداد، مما أفضى إلى نتائج سلبية بالنسبة للعرب المسلمين في الأندلس.